90 Association of post-traumatic stress disorder with work performance amongst emergency medical service personnel, Karachi, Pakistan. (1st September 2016) - Kerai, Salima; Islam, Muhammad; Khan, Uzma; Asad, Nargis; Razzak, Junaid; Pasha, Omrana
Abstract : Background: Emergency medical service (EMS) personnel are exposed to various stressors in their day to day functioning. They are exposed to various kinds of stressors which includes but not limited to handling dead children, medical emergencies, severe injuries, acts of violence, organisational problems etc. Their daily exposure to diverse critical and traumatic incidents can lead to stress reactions like Post-Traumatic Stress Disorder (PTSD). Consequences of PTSD in terms of work loss can be catastrophic because of its compound effect on families, which affect them economically, psychologicaly as well as socialy. Therefore, it is critical to assess the association between PTSD and Work performance in Emergency Medical Service (EMS) if exist any. Methods: This prospective observational study was carried out at AMAN EMS in Karachi, Pakistan. EMS personnel were screened for potential PTSD using impact of event scale-revised (IES-R). Work performance was assessed on basis of five variables; number of late arrivals to work, number of days absent, number of days sick, adherence to protocol and patient satisfaction survey over the period of 3 months. In order to model outcomes like number of late arrivals to work, days absent and days late; negative binomial regression was used. Whereas logistic regression was applied for adherence to protocol and linear for patient satisfaction scores Results: Out of 536 EMS personnel, 525 were found to be eligible, of them 518 consented. However data on 507 were included because 7 left the job during study period. The mean scores of PTSD was found to be 24.0 ± 12.2. However, weak and insignificant association was found between PTSD and work performance measures: number of late arrivals (RRadj 0.99; 95% CI: 0.98–1.00), days absent (RRadj 0.98; 95% CI: 0.96–0.99), days sick (Rradj 0.99; 95% CI: 0.98 to 1.00), adherence to protocol (ORadj 1.01: 95% CI: 0.99 to 1.04) and patient satisfaction (0.001% score; 95% CI: −0.03% to 0.03%). Conclusion: Higher score of PTSD were found among EMS personnel signifying their exposure to range of stressful incidents from handling violence to trauma and other medical emergencies. No association was found between PTSD and Work performance in the selected EMS population in Karachi Pakistan. Further studies are needed to explore the phenomenon of resiliency in this population.